Regulatory microRNA - Taguchi, Y-h.; Wang, Hsiuying (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
This book includes updated information about microRNA regulation, for example, in the fields of circular RNAs, multiomics analysis, biomarkers and oncogenes. The variety of topics included in this book reaffirms the extent to which microRNA regulation affects biological processes. Although microRNAs are not translated to proteins, their importance for biological processes is not less than proteins. An understanding of their roles in various biological processes is critical to understanding gene function in these biological processes. Although non-coding RNAs other than microRNAs have recently come under investigation, microRNA still remains the front runner as the subject of genetic and biological studies. In reading the collection of papers, readers can grasp the most updated information regarding microRNA regulation, which will continue to be an important topic in genetics and biology.
English
Keywords: microRNAs; porcine vein graft and stent models; autophagy regulator; parkinson$1 (Bs diseases; miR-133a-5p; embryogenesis; circular RNA; miR-30a-3p; skeletal muscle; azacitidine; miRNA-mRNA integration; circHIPK3; autophagy; gene; smooth muscle cells; myelodysplastic syndromes; bone formation; transcriptional factor; Teleostei; MEG3; regulatory network; RNA interference; non-coding RNA; 14q32; miR-29b-1-5p; miRNA-gene target interaction; osteogenesis; virus; passenger miRNA; target prediction; inflammation; miRNA; oncolytic virotherapy; ischemic stroke; extracellular vesicles; proliferation; post-transcriptional gene regulation; amyotrophic lateral sclerosis (ALS); prognosis; epigenetic biomarker; angiogenic-osteogenic coupling; sequence-nonspecific off-target regulation; calf; GPER; bone angiogenesis; osteomiRs; FGFR2; tensor decomposition; therapeutics; circFGFR2; small interfering RNA; RWR algorithm; Cyclin D1; muscle biopsy; tissue-enriched miRNAs; host; bone regeneration; development; cerebrospinal fluid (CSF); miRNA sequencing